2019
DOI: 10.7759/cureus.5968
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Among Healthcare Professionals Regarding Contaminated Stethoscopes as a Source of Nosocomial Infections

Abstract: ObjectivesThe objective of this study was to determine the awareness among healthcare professionals regarding stethoscopes as a source of nosocomial infections, their cleaning practices in this regard before or after examination, and to find out about the existence of any guidelines and accountability criteria issued by the hospitals in this regard.MethodologyA descriptive cross-sectional study of 243 healthcare professionals using non-probability convenience sampling was done to include consultants, residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, awareness of possible transmission due to equipment used by anesthesiologists may be lacking. A study of awareness among healthcare clinicians regarding stethoscopes as a possible source of nosocomial infection reported that most believed that their hospitals did not have protocols for disinfecting stethoscopes and there was no accountability regarding this [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, awareness of possible transmission due to equipment used by anesthesiologists may be lacking. A study of awareness among healthcare clinicians regarding stethoscopes as a possible source of nosocomial infection reported that most believed that their hospitals did not have protocols for disinfecting stethoscopes and there was no accountability regarding this [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, only 9.5% cleaned their stethoscope per patient, 20.6% did it daily, 19.8% did it weekly, 16.9% did it monthly, 14.9% did it six-monthly while 28.4% respondents had never cleaned their stethoscope. Of note, 99.2% believed that there were no accountability criteria set for the assessment of the cleanliness of stethoscopes in their hospitals [33].…”
Section: Disinfecting Practicesmentioning
confidence: 99%
“…International research shows high bacterial contamination of stethoscopes, with most participants aware of their potential to spread nosocomial infections. However, only 9.5% clean them after each use, with alcohol wipes being the most commonly used cleaning product (14). HAIs often stem from hygiene neglect, a common cause of medical malpractice claims.…”
Section: Introductionmentioning
confidence: 99%